Hydrothermally Treated TiO2 Nanorods as Electron Transport Layer in Planar Perovskite Solar Cells - Chawalit Bhoomanee (2020)
© 2020 Wiley-VCH GmbH The development of metal oxide-based electron transport layers in perovskite solar cells (PSCs) has received intensive research interest for achieving high-efficiency PSCs. Herein, TiO2 nanorods (TiO2 NRs) are grown onTiO2 seed layers coated on fluorine-doped tin oxide (FTO) glass substrate by using a hydrothermal method and then are utilized as the electronic transport layer in PSCs. The main concern, after hydrothermal growth of TiO2 NRs, is that their crystallinity can be improved by a sequential high-temperature treatment at 450 °C. In addition to high-temperature annealing, a low-temperature treatment with boiling water, which is expected to clean the surface of the TiO2 NRs, is developed. In this contribution, the champion PSCs are those based on TiO2 NRs where boiling water treatment achieves a maximum power conversion efficiency (PCE) of 15.50%, whereas a PCE of 12.91% is obtained from PSCs based on TiO2 NRs with high-temperature annealing. The remarkable ease of using a water-assisted process offers an efficient approach to the removal of residuals adsorbed on the surface and circumvents the disadvantage of a thermal annealing method resulting in high-production costs. This low-temperature treatment can be used to improve TiO2 films in flexible PSCs.